Perfil clínico-epidemiológico da Criptococose em pacientes HIV positivos atendidos em uma unidade de referência em Belém do Pará - ALMEIDA, Jairo Cunha de (Universidade Federal do Pará, 2013)
Cryptococcosis among residents of the state of Pará presents as severe endemic disease, occurring in different mesoregions state end the metropolitan area of Belém occurscausing cryptococcal meningitis, with a mortality rate above 40%. To try to elucidate the clinical end epidemiological study of cryptococcosis in HIV-positive patients, we conducted a retrospective study, analytical case series with chart review of the last 05 year (2006 – 2010), with HIV-positive patients in a referral hospital in Belém- Pará. The disease is still one of the most frequent causes of death in HIV-positive patients in our region and due to C. neoformans the largest number of cases, accouting for 57 (60,6%) ot a total of 94 cases. Regarding the clinical form of cryptococcosis, developed by the HIV-positive patients, we observed that the nervous system is present in 46,8% of patients and the spred of disease in 27,7% of cases. The relationship between the cause of deathand the presence of Cryptococcus occurs by a complex set of factors that must be clarified and correlated with patient death end most importantly, establisn qua strong in this relationship once detected.